Efeitos do LPS bacteriano nos processos funcionais e de diferenciação de células progenitoras da polpa dentária - Ferreira, Luciana Corrêa [UNESP] (2014)
Dental pulp repair processes due to conservative procedures are, in general, affected by the conflicts between possible microorganisms at the area of exposure and cells responsible for differentiation and production of mineralized tissue. However, the literature still lacks information on how bacterial products affect these processes directly. The purpose of this study was to evaluate the bacterial lipopolysaccharide (E. coli LPS) effects on dental pulp progenitor cells, regarding the expression of differentiation genes and function of mineralization, using basal conditions and pre-induced mineralization by osteogenic media. Characterized progenitor cells was initially submitted to different LPS concentrations (with or without osteogenic medium [lM]), to observe alkaline phosphatase activity (ALP). The minimal concentration (200 ng/ml) to observe phosphatase enzymatic activity was used to assess the functional mineralization effects (by alizarin red staining - ARS), cytokine production (IL-1β e TNF-α), besides the gene expression for odontoblast differentiation markers (DSPP and DMP-1). Quantitative data will be statistically analyzed by ANOVA and Tukey's test. Cells in osteogenic medium with different concentrations of LPS showed low ALP activity shortterm compared to those treated with α-MEM. These showed high activity, compared to control. 200 ng/ml of LPS did affect the mineralization process over time, reducing the action of mineralization of the groups that have associated LPS with the IM. There was expression of IL-1β and TNF-α for all groups at all times, additionally, IL-1β for the group that has associated 200 ng/ml of LPS with osteogenic media after 7 days showed higher expression. There was expression of DMP-1 and DSPP genes and the expression in groups treated with IM was greater in DMP-1. These findings suggest that the inflammatory potential of LPS on the pulp progenitor cells contribute to an early mineralization ...